Relationship between sires’ estimated breeding value for first lactation and lifetime traits in Sahiwal and Hariana cattle - PUNDIR, R K; RAHEJA, K L (The Indian Journal of Animal Sciences, 2013)
Data Oil Hariana and Sahiwal cows sired by 46 and 39 sires, respectively, and maintained at U.P. State Govemment Livestock farms at Chack Ganjaria and Bubugarh, were used to evaluate sires for first lactation and lifetime productivity. First lactation traits included in lhe study were age at first calving, total lactation milk yield, 300-day milk yield and lactation length. Lifetime traits were herdlife, lifetime milk yield, productive life, number of days in milk and number of lactations completed. A multi-trait best linear unbiased prediction (BLUP) procedure was used to estimate sire’s breeding value. Multi-trait mixed model included the year-season of calving and sire genetie group as random effect. The estimates of Tank and product moment correlations among estimates of sire’s breeding value indicated that all sires would not rank same for first lactation and lifetime performance traits. However, the ranks of sire for different traits revealed that 4-5% of top sires almost had similar rank for firstlaetation and lifetime traits. Results suggest that major culling of bulls to be used to breed cows should be doneon the basis of first lactation traits. To improve the lifetime productivity of dairy animal, evaluation of dairy sires for lifetime traits conld be used as additional criteria for the bulls to be used as sires of future bulls.